Incidence and clinicohematological profile of lymphomas in Southern Punjab Pakistan - Saleem, Umera; Naveed, Muhammad Asif; Batool, Maria; Nadeem, Khadeeja; Muhammad Sami ullah; Safdar, Sohail (International Journal of Endorsing Health Science Research, 2020)
Background: Lymphomas are ranked as the sixth most common malignancy worldwide. Endorsing a significant impact on the health sector among the developing countries like Pakistan. The aim of the current study was to estimate the burden and clinicopathological features of lymphomas in one of the major referral centers in Southern Punjab Pakistan. Methodology: A descriptive cross-sectional study was conducted at the Pathology department of Nishtar Medical University, Multan January 2016 to August 2019. A total of 74 patients both male and females of all age groups with diagnosed lymphoma were enrolled in the study. Diagnosis was made on morphology and immunohistochemistry of lymph node and cases with complete immunohistochemical workup were included and those without immunohistochemical panel were excluded from the study. Baseline tests were performed and bone marrow specimens were extracted from all cases. The data was analyzed using SPSS Version 23.0. Results: Out of the total, 22.6% patients had Hodgkin lymphoma (HL) and 77.4% had Non-Hodgkin lymphoma (NHL). Classical Hodgkin lymphoma (CHL) was the most frequent histology (94%) among HL patients while Diffuse large B cell lymphoma (DLBCL) was the commonest B cell NHL (29.3%) and T cell lymphoblastic lymphoma (T-LBL) was found to be the most common T cell variant (5.3%). B symptoms, splenomegaly and hepatomegaly were documented in 96%, 42.7% and 25.3% patients respectively. Moreover, the disease was nodal in 65% cases and extranodal presentation was observed in 35% of the cases. Cervical node (lymph node) was involved in 25.3% of the cases while bone marrow was common among 53.3% cases. The patterns of bone marrow infiltration were para trabecular (24.3%), diffuse (22.5%), interstitial (1.8%) and mixed pattern (3.75%). Conclusion: Lymphomas are relatively more common among younger population in Pakistan. NHLs constitute more than 2/3rd of all lymphomas with DLBCL as the commonest histology. Stage IV disease as evidenced by bone marrow infiltration is seen in more than half of our patients.